2007
DOI: 10.1007/s00330-007-0754-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the chest in children (mediastinum excluded)

Abstract: Ultrasound (US) of the paediatric chest has become an established imaging tool that may supplement plain film findings helping to reduce or tailor other ionizing (sectional) imaging in a variety of paediatric conditions such as sequestration or pneumonia. US has been shown to offer valuable imaging alternatives, both reliably enabling diagnosis without need for ionising imaging such as in diaphragmatic palsy (traditionally diagnosed by fluoroscopy) and revealing additional information in patients with equivoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 51 publications
0
52
0
2
Order By: Relevance
“…5) and (d) homogenously echogenic. Moreover, chest US has been shown to be more sensitive than CT in demonstrating the presence of septa inside a pleural effusion (30) as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 96%
“…5) and (d) homogenously echogenic. Moreover, chest US has been shown to be more sensitive than CT in demonstrating the presence of septa inside a pleural effusion (30) as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies showed that the ultrasound signs of lung and pleural diseases described in adults are also found in pediatric patients [45,[65][66][67][68]. In suspected pneumonia, lung ultrasound has demonstrated to be no less accurate than CXR.…”
Section: P-d4-s9 (Strong: Level A)mentioning
confidence: 99%
“…A mellkas vizsgálható supraclavicularis, suprasternalis, parasternalis, intercostalis subxyphoidealis és transdiaphragmalis betekintésből, a beteg helyzete változtat-ható, ami tovább javítja a lehetőségeket [45,46,47,48,49].…”
Section: Mellkasi Megbetegedésekunclassified